Photophysical, photooxidation, and biomolecule-interaction of meso-tetra(thienyl)porphyrins containing peripheral Pt(ii) and Pd(ii) complexes. Insights for photodynamic therapy applications. Issue 4 (11th January 2022) - Tisoco, Isadora; Donatoni, Maria Carolina; Victória, Henrique Fernandes Vieira; de Toledo, José Roberto; Krambrock, Klaus; Chaves, Otávio Augusto; de Oliveira, Kleber Thiago; Iglesias, Bernardo Almeida
Abstract : Novel Pt(ii )- and Pd(ii ) cationic porphyrins in photobiological process applications. Abstract : We report the synthesis and characterization of two novel tetra-cationic porphyrins, containing Pt(ii ) or Pd(ii ) polypyridyl complexes attached at the peripheral position of N4 -macrocycle. Compounds were characterized through elemental analysis, molar conductivity, cyclic voltammetry, and spectroscopy analysis. Photophysical and photobiological parameters were also evaluated. Also, the binding capacity of each porphyrin with human serum albumin (HSA) was determined by UV–Vis, steady-state, and time-resolved fluorescence spectroscopy, combined with molecular docking calculations. The results suggest that the interaction of these compounds is spontaneous, weak to moderate, and probably occurs at site III (subdomain IB) by non-covalent forces, including van der Waals and H-bonding. Moreover, porphyrins containing peripheral complexes improve their interactions with biomolecules, show good photostability, generate reactive oxygen species under white light studied by electron paramagnetic resonance (EPR) analysis, and promote photo-damage of HSA.